Dialogs: Reading and Writing in the Disciplines - Carroll, Jeffrey (New York Macmillan Publishing Company, 1992)
A unique reader that encourages students to engage in both informal and formal "conversations" with the great traditions, issues, and current arguments of certain disciplines. Offering selections that are genuinely a part of academic discourse and texts that are written and read by academics, Dialogs provides true examples of the types of writing used and valued in the university.
Keywords: Writing